Effects of Aging Temperature on Moisture Absorption of Perforated GFRP - Shiva Eslami; Fathollah Taheri-Behrooz; Farid Taheri (Advances in Materials Science and Engineering)
This paper examines the effects of aging on the flexural stiffness and bending loading capacity of a perforated glass fiber-reinforced epoxy composite subjected to combined moisture and elevated temperature. Specimens, in the configuration of one-quarter of a perforated GFRP tube, were aged in 60% humidity and temperatures of 40, 60, and 80°C, respectively. Moisture absorptions of the specimens were measured during the aging process, and bending tests were conducted on the specimens after aging. The SEM images were also captured to further examine the effects of the moisture absorption on the aged specimens. The results indicated that the increase in the aging temperature reduced the diffusion coefficient, thus inducing more moisture absorption by the composite and in turn causing more reduction in composite’s flexural stiffness and bending capacity. Moreover, the ability of Fick’s equation for predicting the moisture absorption rate in such perforated thin-walled composite configuration at various moisture contents and temperatures was also assessed. A semiempirical equation was developed and proposed by which the reduction of the stiffness in the perforated aged GFRP structures could be predicted.